Antioxidant Activity of Premna serratifolia Linn. Leaf Extracts: A Comprehensive Analysis Using Various Testing Methods - Muhaimin, Muhaimin; Iskandar, Yoppi; Hazrina, Aghnia; Hirzan, Rifanza; Khatib, Alfi; Syahri, Wilda (Indonesian Food Science and Technology Journal, 2024)
Premna serratifolia Linn leaf possesses medicinal properties, useful in the treatment of cardiovascular diseases, skin diseases, inflammatory diseases, arthritis, rheumatism, anorexia, jaundice, intestinal worms, bad breath, lung infections, febrifuge, hypolipidemic, antioxidants, antidiabetic, CNS depressant and thalasemia treatment, among other things. The purpose of this study was to investigate the antioxidant effect of P. serratifolia Linn leaf from Indonesia. The leaves of P. serratifolia Linn were extracted with 95% ethanol and fractionated with n-hexane and ethyl acetate. The antioxidant activity was evaluated by various antioxidant assays, including  1-diphenyl-2-picrylhydrazyl (DPPH), 2’-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS), nitric oxide scavenging and reducing power ability method. The extracts and fractions contained phytoconstituents such as alkaloid, flavonoid, phenolic, tanin, saponin, and steroid compounds, according to phytochemical analysis. The antioxidant activities were compared to standard antioxidant ascorbic acid. P. serratifolia Linn ethanol leaves extract showed a significant antioxidant activity in DPPH, ABTS, reducing power and nitric oxide scavenging methods compared others. The findings of the present study suggest that P. serratifolia Linn could be a potential source of natural antioxidant that could have greater importance as therapeutic agent in preventing or slowing oxidative stress related degenerative diseases.